COVID-19 Pandemic and Its Impact on Perinatal Outcomes between Symptomatic and Asymptomatic Women. (14th July 2022) - Babic, Inas; Alsomali, Faten; Aljuhani, Sana; Baeissa, Sahar; Alhabib, Inam; AlAhmari, Ebtisam; Omer, Magdy; Alkhalifa, Khalid
Abstract : Coronavirus disease 2019 (COVID-19) has been increasing among pregnant women worldwide. Its impact on maternal, fetal, and neonatal health is still scarce in the published literature. As a routine COVID-19 prenatal screening has been established for all women requiring hospitalization, it is not clear whether symptomatic women carry worse pregnancy outcomes than those without symptoms. We aimed to analyze perinatal outcomes between symptomatic and asymptomatic women admitted to our center. Materials and Methods . A single-center retrospective cohort study was conducted for fourteen months. All pregnant women with positive reverse transcriptase-polymerase chain reaction (RT-PCR) test results for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) were enrolled, and their perinatal outcomes were analyzed in two groups based on whether they were symptomatic or not. The primary outcomes were composite adverse fetal, neonatal, and maternal outcomes and their comparison between study groups. Results . Out of 209 included COVID-19 positive pregnant women, 62 (30%) presented with one or more infection-related symptoms. Symptomatic women were older, multiparous, carried ≥1 comorbid condition, and attained infection at earlier gestational age (44% vs. 28%; 82% vs. 69%; 28% vs. 16%; and 34 vs. 36 weeks, respectively) (p < 0.05 ), when compared to asymptomatic women, respectively. Maternal composite adverse outcomes were higher in the symptomatic group and showed either one or more outcomes, positive chest radiological findings, requiring hospitalization with oxygen supplementation, or maternal death (8% vs. 0.7%) (p < 0.05 ). Composite fetal and neonatal adverse outcomes such as miscarriage, fetal or neonatal death, admission to neonatal intensive care unit, and neonatal COVID-19 infection were not statistically significant (p > 0.05 ) between symptomatic and asymptomatic women. Conclusion . COVID-19 infection among symptomatic pregnant women may carry a higher risk for adverse maternal outcomes. It may be associated with their advanced age and comorbid conditions. Maternal infection-associated symptoms per se likely do not pose an increased risk for adverse fetal or neonatal outcomes.